2017
DOI: 10.1096/fj.201700097r
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged darkness reduces liver fibrosis in a mouse model of primary sclerosing cholangitis by miR‐200b down‐regulation

Abstract: Melatonin therapy or prolonged exposure to complete darkness reduces biliary hyperplasia and liver fibrosis in bile-duct-ligated (BDL) rats; however, no information exists in primary sclerosing cholangitis (PSC). Thus, we aimed to determine the therapeutic effects of prolonged dark therapy or melatonin administration on hepatic fibrosis in the multidrug resistance gene 2-knockout (Mdr2) mouse model of PSC. Melatonin levels, biliary mass, liver fibrosis, angiogenesis and miR-200b expression were evaluated in wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 38 publications
6
76
1
Order By: Relevance
“…Several miRNAs are dysregulated during melatonin treatment for malignancies and hepatic disorders . Recently, Marques et al demonstrated that melatonin inhibits breast cancer progression by targeting miR‐152‐3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs are dysregulated during melatonin treatment for malignancies and hepatic disorders . Recently, Marques et al demonstrated that melatonin inhibits breast cancer progression by targeting miR‐152‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…microRNAs (miRNAs), small noncoding RNAs that regulate protein production by controlling gene expression at the post‐transcriptional step, mediate the effects of melatonin in cancer and liver disease . In a recent study, miR‐590‐3p was found to mediate melatonin‐enhanced cell apoptosis in human osteoblasts .…”
Section: Introductionmentioning
confidence: 99%
“…Mdr2 −/− mice are the most common mouse model for human PSC, which have similar conditions such as cholestasis, biliary inflammation, ductular reaction, and liver fibrosis . Dark therapy (complete dark for 1 week) or melatonin administration (2 mg/g body weight per day for 1 week via drinking water) for Mdr2 −/− mice improved liver conditions compared to control Mdr2 −/− mice with 12:12 hours light‐dark cycle by inhibiting expression of VEGF‐A/C in cholangiocytes via decreased levels of microRNA (miRNA) miR‐200b . Thioacetamide (TAA) induces biliary damage in rodents and utilized as a model of cholestatic liver injury .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…Liver steatosis was reported to be ameliorated by melatonin via miR-23a [24]. In murine model of liver fibrosis, melatonin reduced primary sclerosing cholangitis by downregulating miR-200b in cholangiocytes and stellate cells [25]. Studies on miRNAs in Alzheimer's disease (AD) are of particular interest, because neuroinflammation, which is fueled by Aβ peptides and oligomers, can be partially reversed by melatonin [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat scopolamine toxicity model of ADlike memory losses, melatonin reversed an increase of miR-124 and thereby corrected the level of the targeted Egr1 (early growth response protein 1) mRNA [27]. In another AD model, Aβ [25][26][27][28][29][30][31][32][33][34][35] peptide added to primary cortical neurons caused downregulation miR-132, an effect that was also reversed by melatonin. The normalization of miR-132 is insofar of importance, as this miRNA transmits anti-apoptotic and other protective properties known from melatonin [28].…”
Section: Discussionmentioning
confidence: 99%